The Important Role of Knowledge Sharing in Improving Business Performance of Traditional Central Kalimantan Food Restaurants - Ferdinand; Peridawaty (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community service by providing education at traditional restaurants in Central Kalimantan needs to be carried out well and in a focused manner. Currently, reporting on restaurant income or profits is starting to improve with the existence of social media as a medium for information and promotion. As is done in traditional restaurants in Central Kalimantan, it is stated that knowledge sharing is important in improving business performance which has an impact on income. This activity is carried out annually in order to provide direct implementation of business digital media as a cheap, easy and fast knowledge sharing medium. These results also indicate that product quality must always be carefully considered, because food is very vulnerable to public health.